Genotype-environment interaction in multibreed bovine populations in the colombian low tropic (2010)
ABSTRACT: With the aim of quantifying the genotype-environment interaction (GEI) and the phenotypic stability in multibreed bovine population of the Colombian Northwest, registries from 16 herds located in three agroecological regions (E1, E2, E3) from low tropic systems (humid subtropic forest, humid tropic forest and dry tropic forest, were collected from 1995 to 2007. Weight at 12-mo (W12), weight at 18-mo (W18), and weight at 24-mo (W24), were evaluated with 1806, 1455, and 1197 data, 14, 11, and 10 genetic groups respectively; animals of the breeds and crossbred between Angus (A), Blanco Orejinegro (B), Zebu (Z), Holstein (H), Romosinuano (R), and Senepoll (S) were used. In a mixed model, the fixed effects of contemporary group (year-season-sex) and the age covariate were used, which showed a significant effect (p‹0.001) on the three traits. Random effects were region, genetic group (breed or crosses), and GEI, but the last one (GEI) showed significant effect (p‹0.05) for this last one. The Shukla’s variance in Bayesian methodology was used for the phenotypic stability analysis. The results indicated that the groups with high proportion of Zebu were associated with E2 and groups with greater levels of Romosinuano were associated with E3. Holstein and Blanco Orejinegro tended to give greater phenotypic stability than the groups that used these breeds.